2022
DOI: 10.1091/mbc.e22-05-0189
|View full text |Cite
|
Sign up to set email alerts
|

A role for Nup153 in nuclear assembly reveals differential requirements for targeting of nuclear envelope constituents

Abstract: Assembly of the nucleus following mitosis requires rapid and coordinate recruitment of diverse constituents to the inner nuclear membrane. We have identified an unexpected role for the nucleoporin Nup153 in promoting the continued addition of a subset of nuclear envelope proteins during initial expansion of nascent nuclei. Specifically, disrupting the function of Nup153 interferes with ongoing addition of B-type lamins, lamin B receptor (LBR), and SUN1 early in telophase, after the nuclear envelope (NE) has in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…In somatic cells, NUP153 has diverse roles including regulating the export of mRNAs, 16 building chromatin architecture through interactions with CTCF and cohesins, 17 nuclear membrane. 18 In spermatids, the NL is composed of B-type lamins and it is dismantled during spermiogenesis. 19,20 NUP153 might therefore also facilitate B-type lamin extraction from the nucleus and contribute to the breakdown of the spermatid nuclear lamina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In somatic cells, NUP153 has diverse roles including regulating the export of mRNAs, 16 building chromatin architecture through interactions with CTCF and cohesins, 17 nuclear membrane. 18 In spermatids, the NL is composed of B-type lamins and it is dismantled during spermiogenesis. 19,20 NUP153 might therefore also facilitate B-type lamin extraction from the nucleus and contribute to the breakdown of the spermatid nuclear lamina.…”
Section: Discussionmentioning
confidence: 99%
“…We identified that the infertile man 13‐4587 9 is heterozygous for a potential pathogenic variant, p.Pro485Leu, in the nucleoporin NUP153, a critical component of the NPC nucleoplasmic basket. In somatic cells, NUP153 has diverse roles including regulating the export of mRNAs, 16 building chromatin architecture through interactions with CTCF and cohesins, 17 and post‐mitotic formation of the nuclear lamina through the targeting of B‐type lamins to the inner nuclear membrane 18 . In spermatids, the NL is composed of B‐type lamins and it is dismantled during spermiogenesis 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in this in vitro analysis system, the NE subdomain was not observed. Differential accumulation of INM proteins on chromosomes at the early step of NE assembly seems to be a general phenomenon in human cells (Maeshima et al, 2006) and has been precisely described in HeLa cells (Clever et al, 2012;Haraguchi et al, 2001;LaJoie et al, 2022). Therefore, we attempted to reconstitute an in vitro NE reassembly system in human cells that would recapitulate the phenomena observed in living mitotic cells.…”
Section: Introductionmentioning
confidence: 99%